Educational Media Effectively Prevent Postpartum Depression: A Systematic Review - Yessi Priskila; Ani Margawati; Soeharyo Hadi Saputro; Ariawan Soejonoes; Bagoes Widjarnoko; Alifiati Fitrikasari (Poltekkes Kemenkes Palu, 2026)
Background: The prevalence of detected postpartum depression (PPD) ranges from 10-25% of total deliveries. The impact of this condition does not only end with the mother but also has the potential to generate recurring cycles of mental health disorders in children if left unaddressed. Education is the most widely developed and successful intervention. This systematic review aims to evaluate the effectiveness of educational media in preventing postpartum depression. Methods: This study is a systematic review following the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. The databases searched included PubMed, Scopus, and Google Scholar, covering articles published between 2010 and 2023. The inclusion criteria focused on studies using educational media interventions, while exclusion criteria removed articles lacking clear PPD-related outcomes. Of 296 articles identified, 6 studies met the inclusion and exclusion criteria. Results: The review findings indicate that the most developed models are Psychoeducation, Cognitive Behavioral Therapy Education, and Socioeducation. All three models are effective in addressing PPD. However, Psychoeducation is the most feasible medium for model development, given its accessibility, ease of implementation, and positive patient outcomes. Conclusion: These findings suggest that integrating psychoeducation into maternal health programs could serve as a practical and scalable intervention to reduce the risk of postpartum depression.